"Teacher, I know how to do it": An engineering design-based STEM activity on the concepts of forces and floating/sinking for young problem solvers. (2nd January 2023) - Ata-Aktürk, Aysun
Abstract: This article aims to implement an engineering design-based STEM activity for young children and evaluate the implementation process of the activity, along with providing some revision ideas. The activity was held as a 90-minute weekend workshop with the participation of six children aged four to seven. Data were collected through digital observations and field notes. In the activity, the children followed a four-step engineering design process. They solved the cartoon characters' problem by designing a floatable boat that could take the characters across the lake. In addition, the children tried to move their toy boats on the water without touching them. Throughout the activity, children gained hands-on experience with the concept of force. They made predictions about and tested what material would suit their designs. Thus they had the opportunity to think about what might affect the sinking or floating of objects in the water. They heard each other's ideas and observed the testing process of both their own and other children's designs. In all these respects, this article suggests that playful and developmentally appropriate engineering design challenges can be effective in creating STEM mindsets. This article also includes some revision ideas for integrating activity into the curriculum in early childhood education settings in line with the experiences obtained from the implementation process.